Cut-Off Value of Medial Meniscal Extrusion for Knee Pain - Hiroaki Kijima; Naohisa Miyakoshi; Yuji Kasukawa; Yoshinori Ishikawa; Hayato Kinoshita; Kentaro Ohuchi; Masazumi Suzuki; Nozomi Kaga; Chie Sato; Shuichi Chida; Yoichi Shimada (Advances in Orthopedics)
Purpose. Medial meniscal extrusion (MME) has attracted attention as an index of knee pain in conjunction with clinical symptoms that could be more useful than the diagnosis of knee osteoarthritis on X-ray. However, the size of MME that would cause knee pain has not been clarified. The aim of the present study was to investigate the cut-off value of MME for knee pain. Methods. A total of 318 knees were evaluated. The presence of current or past knee pain was confirmed by interview. Next, MME was measured using vertical sonographic images of the medial joint spaces during weightbearing. Results. Overall, 71 knees were painful (P-group), and 247 knees were not (N-group). MME was 5.9 ± 1.8 mm in the P-group and 2.9 ± 1.5 mm in the N-group (P<0.0001). Analysis of the receiver operating characteristic curve showed that the cut-off value of MME for knee pain was 4.3 mm, with sensitivity of 0.8451 and specificity of 0.8502. In addition, 64% of knees without pain cases at the time of examination whose MME exceeded this cut-off value had past knee pain. Conclusions. The sensitivity and specificity of MME for knee pain were very high with a cut-off value of 4.3 mm.